Bronchoalveolar lavage fluid cellular characteristics, functional parameters and cytokine and chemokine levels in interstitial lung diseases - Koziar Vašáková, Martina; Šterclová, Martina; Kolesár, Libor; Slavčev, Antonij; Pohunek, Petr; Šulc, Jan; Skibová, Jelena; Stříž, Ilja (Scandinavian journal of immunology, 2009)
Idiopathic pulmonary fibrosis (IPF), hypersensitivity pneumonitis (HP) and sarcoidosis belong to interstitial lung diseases (ILD) where an imbalance of regulatory, profibrotic and antifibrotic cytokines is hypothesized. The relationship of bronchoalveolar lavage (BAL) fluid (BALF) cytokines, BALF cell profile and ILD course is supposed. The aim of our study was to correlate BALF cytokine and chemokine levels with BALF cellular characteristics and lung function parameters in different ILD. Twenty-two sarcoidosis, seven IPF and 11 HP patients underwent lung function tests and BAL. The BALF differential cell counts and superficial cell markers were characterized, and MCP-1, MIP-1alpha, MIP-1beta, RANTES, epithelial neutrophil-activating protein (ENA)-78, FGF, G-CSF, GM-CSF, IFN-gamma, interleukin (IL)-1alpha, IL-1RA, IL-1beta, -2beta, -4beta, -5beta, -6beta, -8beta, -10beta, -17beta, tumour necrosis factor (TNF)-alpha, thromobopoietin (Tpo) and vascular endothelial growth factor (VEGF) values measured. The BALF VEGF values were highest in sarcoidosis (P = 0.0526). IL-1RA values were higher in IPF and HP compared with sarcoidosis (P = 0.0334). IL-8/ENA-78 ratio positively correlated with BALF neutrophil counts in IPF (r = 0.89, P = 0.04). Vital capacity and TL(CO) values positively correlated with VEGF and negatively with IL-8 BALF levels in all ILDs but the correlations were most significant in sarcoidosis group. We suppose that VEGF plays a role in ILDs' early phases and has rather angiogenic than profibrotic effect. On the contrary, IL-8 is probably upregulated in advanced ILDs with prominent fibrosis and marked lung functions decline. We state that BALF VEGF, IL-8 and ENA-78 levels and IL-8/ENA-78 ratio could become useful markers of ILDs' phase, activity and prognosis. They might also be helpful in treatment modality choice.
Keywords: financování organizované; bronchoalveolární lavážní tekutina; Cell Count; Bronchoalveolar Lavage Fluid; Female; Cytokines; intersticiální plicní nemoci; ženské pohlaví; cytokiny; lidé; bronchoalveolární laváž; Financing, Organized; Male; Lung Diseases, Interstitial; Bronchoalveolar Lavage; počet buněk; lidé středního věku; Respiratory Function Tests; mužské pohlaví; respirační funkční testy; Middle Aged; Humans